Arthrodesis of Interphalangeal Joints and Fixation of Phalangeal Fractures in Trauma-Preliminary Report of a Simple Technique - Koshy, Cherian M.; Shankarappa, Yedu; Guido, Norman L. (Indian Journal of Plastic Surgery, 1989)
An improvised external fixator consisting of ‘K’ wires and acrylic resin was used in five cases of finger trauma. Rigid fixation with compression for arthrodesis was used in two cases to restore functional finger position; in three cases the same method was used to fix phalangeal fractures. Results were excellent and the method proved simple and rewarding.